Proceedings of the International Conference of Science and Technology for the Internet of Things 2019
DOI: 10.4108/eai.19-10-2018.2282613
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Think Talk Write Model in English Essay Writing

Abstract: The aim of this study is to examine the effect of think talk writes learning model on English essay writing ability of English Education Program Study at STKIP Bandar Lampung. The research sample was 22 semester IV students. The process of collecting data through observation, interviews and tests. The technique of data analysis is t-test independent. While the process of data validity used credibility, transferability, dependability, and conformability. The results of the research show that the mean of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The results suggest that students may have recorded evidence of tighter correction between their revised skill assessments and their actual performance after self-regulated strategy development instruction. Also in Istiara (Istiara, 2019) Based on the research results, Think Talk Write and Self-Regulated Strategy Development were effective in improving students' ability to write recount texts and are proposed to be applied to the teaching process.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that students may have recorded evidence of tighter correction between their revised skill assessments and their actual performance after self-regulated strategy development instruction. Also in Istiara (Istiara, 2019) Based on the research results, Think Talk Write and Self-Regulated Strategy Development were effective in improving students' ability to write recount texts and are proposed to be applied to the teaching process.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (e.g., Darmawangsa, Mutiarsih, Karimah and Racmadhany, 2020; [5] Herlina, Rahman, and Abdul, 2022; [8] Istiara, 2018; [10] Kamilia, 2019; [12] Kurniaman, Yuliani and Mansur, 2018; [13] Laoli and Harahap, 2021; [14] Muna, Aziz, and Muthalib, 2020; [18] Nova, Umara, and Ginting, 2022; [19] Qomariyah and Nafisah, 2020; [21] Rahmah, 2017) [23] confirmed that TTW strategy is useful and successful as a teaching strategy. It also revealed that a few studies have been conducted to investigate the effect of TTW strategy on students' writing performance at school and university level.…”
Section: Discussionmentioning
confidence: 99%
“…Istiara (2018) [10] investigated the impact of TTW strategy as a learning model on English essay writing ability. The participants of the study were 22 semester IV students.…”
Section: Review Of the Related Literaturementioning
confidence: 99%